Interactive effects of a calcium and magnesium sulphate enriched waste water on crop growth and nutrition - Claassens, Andries Stephanus (University of Pretoria, 2013)
Dissertation (MSc (Plant Production and Soil Science))--University of Pretoria, 2007.